Comparative Efficacy of Different Medicaments for Induction of Estrus in True Anestrus Jafarabadi Buffalo Heifers - Raval, Rupesh; Parmar, Kiran; Vala, Karshan; Solanki, Gajendra; Parikh, SS (Indian Journal of Veterinary Sciences and Biotechnology, 2015)
The relative efficacy of different treatment modalities was evaluated for induction of estrus in 32 post-pubertal true anestrus Jafarabadi buffalo heifers randomly divided into four equal groups. Animals of Group I received intravaginal CIDR and i/m injection of 1.0 mg estradiol valerate on day 0, i/m injection of 500 µg PGF2α on day 7 while removing CIDR, and 0.75 mg estradiol valerate on day 8. Fix timed insemination (FTAI) was performed at 48 and 72 h following PGF2α injection. Animals of Group II received standard Ovsynch protocol with FTAI. In Group III, Prajana HS 3 caps/ day for 3 days along with i/m injection of Vitamin AD3E (5 ml) and Tonophosphan (15 ml) on first day were administered. Group IV animals received no treatment and served as control. Among all inseminated heifers, in non-return cases pregnancy was confirmed per rectum 60 days post breeding. The estrus induction response in Group I and II animals was 100 %, whereas in Group III and IV it was 37.5 % and 12.5%, respectively. In Group I, one animal conceived at induced estrus and another four at second service while in Group II, five animals conceived at second service giving overall conception rate (CR) of 62.5% in each group within 77 days of treatment. In Group III, three animals conceived by 70 days and in Group IV, only one animal (12.5%) showed estrus and conceived by 50 days of treatment with overall CR of 37.5% and 12.5%, respectively. Mean plasma progesterone concentration was significantly (p<0.05) higher on day 7 as compared to day 0, at estrus and on day 20 post-AI in all the animals. It was concluded that both CIDR and Ovsynch protocols are better than herbal heat inducer + supplements in inducing fertile estrus in anestrus buffalo heifers.